Satisfaction of Beekeepers' towards the Services of National Horticulture Mission - Jaya Mehra , K. L. Dangi and Vanpal Kumar Boyal (Indian Journal of Extension Education, 2014)
National Horticulture Mission was launched in the country in May 2005 as a centrally sponsored scheme to promoteholistic growth of the horticulture sector through an area based regionally differentiated strategies. The presentinvestigation was undertaken to evaluate the project with special reference to beekeeping under NHM. The evaluation ofthe programme is essential for making the future programme more effective. Keeping this in view, the present study wasundertaken in Kota district of Rajasthan to study the satisfaction level of the beekeepers towards beekeeping programmeunder National Horticulture Mission. The study indicated that majority (98.00 %) of the beekeepers had high satisfactionlevel towards services provided by NHM for beekeeping programme. Besides, 2.00 per cent were moderately satisfiedwith services provided by NHM. The beekeepers were highly satisfied about storage of produce (MPS 78.94), however,they were least satisfied with availability of bee colonies (MPS 67.40).